The Effect of Using Ecology Modules on Communication Skills, Cognitive, and Student Attitudes Through Problem-Based Learning - Ginanjar, Gigin; Rahayu, Maya; Ayuningtyas, Vidya (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Learning carried out in lectures requires a variety of learning resources to improve students' abilities for the better. During this time, lectures usually only use learning resources that vary little and tend to use only one source so that student learning outcomes are not maximized. This research was conducted to improve student learning outcomes, especially in communication skills and cognitive and student attitudes at Bina Bangsa University. The research method used is ADDIE development research, starting from the stages of Analysis, Design, Development, Implementation, and Evaluation. Module development is carried out by measuring its effectiveness on communication skills using observation sheets, measuring cognitive abilities with tests, and observing attitudes with observation sheets. The application of the module in learning is carried out with a quasi-experimental design. Then, the results are analyzed descriptively with the ANCOVA statistical test using the SPSS application. The results showed improved communication skills, cognitive abilities, and student attitudes. Based on statistical tests, there are differences in the achievement of learning outcomes between the control and treatment classes. In the treatment class, the application of problem-based learning modules showed improved communication, cognitive, and student attitudes. However, based on the value of the gain score, the use of problem-based teaching modules on communication skills and student attitudes is in the range of low effectiveness, while in cognitive aspects, it is in the range of moderate effectiveness. Using ecology modules with problem-based learning is important because real problem-based learning makes learning more contextual, especially in courses that use environmental problems as the main study.